Number of positive lymph nodes affects outcomes in parotid adenoid cystic carcinoma - Han, Feng (Frontiers in Oncology, 2023)
Objectives: Survival significance of the number of positive lymph nodes (LNs) in parotid adenoid cystic carcinoma (ACC) remains unknown; thus, this study aimed to determine the impact of the number of positive LNs on the prognosis of parotid ACC. Methods: Patients with surgically treated parotid ACC were enrolled from the SEER database. The number of positive LNs was analyzed using three models (0 vs 1+, 0 vs 1 vs 2 vs 3 vs 4 vs 4 vs 5 vs 6+, 0/1 vs 2–4 vs 5+), its hazard ratios on disease specific survival (DSS) and overall survival (OS) were assessed using univariate and multivariate Cox analyses. Results: A total of 1,689 patients were included. In all models, the number of positive LNs was independently related to DSS and OS, model 3 had the highest C-index for DSS [0.83 (95% CI: 0.81–0.85)] and OS [0.82 (95% CI: 0.80–0.84)]. Compared with the 0/1 positive LN group, the 2–4 positive LN group had an HR of 2.81 (95% CI: 1.73–4.56) for DSS and 2.36 (95% CI: 1.58–3.54) for OS. The 5+ LN group had an HR of 20.15 (95% CI: 7.50–54.18) for DSS and 14.20 (95% CI: 5.45–36.97) for OS. No overlap existed in the 95% CI of the HR. Conclusions: The three prognostic categories based on the number of positive LNs (0/1 vs 2–4 vs 5+) could stratify the DSS and OS in parotid ACC without overlap.